Caracterização molecular, citogenética e sensibilidade a herbicidas em três populações de Rottboellia cochinchinensis em cana-de-açúcar no estado de São Paulo - Schiavetto, Ana Regina [UNESP] (2015)
The Brazilian high sugarcane production comes from adequate management techniques, which when non-properly used may cause significant yield losses. The weed control is one of these crop practices; such technique consists of eliminating unwelcome plants from farming areas. Among weed species, itchgrass (Rottboellia cochinchinensis) can be highlighted as one of the plants difficult to be controlled. This fact may be associated to a reduced number of selective herbicides registered for sugarcane crop, weed genetic variability, seed dormancy and plant vigor. By means of the difficult chemical control faced by farmers, we have drawn up a hypothesis that such fact might be related to the existence of varied biotypes between and within the different weed populations in sugarcane fields, responding distinctly to herbicide applications. To check this hypothesis, we aimed to study the genetic variability of Rottboellia cochinchinensis (itchgrass) from three different populations (in the cities of Igarapava, Mococa and Piracicaba) in São Paulo State, Brazil, and using AFLP technique. Moreover, post-emergence application and cytogenetics were tested. Upper third leaf and seed samples were collected from the three locations, in areas of sugarcane commercial production. For molecular characterization, six primers were used with the AFLP marker, using 10 plants per population (30 in total), based on band presence (1) and absence (0) in the year of 2012. A completely randomized experiment was set to evaluate herbicide responses, using 20-L pots. Chemical treatments were performed by the herbicides: ametryn (3,000 g ha-1) - T1; isoxaflutole (135 g ha-1) - T2; ametryn (300 g ha-1)+isoxaflutole (135 g ha-1) T3; isoxaflutole (135 g ha-1)+clomazone (1200 g ha-1) T4; amicarbazone (1400 g ha-1) - T5; ametryn (3,000 g ha-1)+trifloxysulfuron-sodium (22.5 g ha-1) - T6; glyphosate (2,160 g ha-1) - T7; MSMA (2,880 g ha-1) - T8 and ametryn ...